Contribution of large pelagic capture fisheries to the GRDP of Sulampua (North Sulawesi, Central Sulawesi, Maluku, and West Papua) in 2019–2023 - Adha Susanto; Erian Febri Satriawan (Universitas Malikussaleh, 2026)
Sulampua areas such as North Sulawesi, Central Sulawesi, Maluku, and West Papua are areas that have large potential for large pelagic fish such as tuna, skipjack, and mackerel (TCT). This study aims to determine the role of TCT capture fisheries on GRDP in four Sulampua areas in 2019–2023. As well as to see how large the utilization level and sustainable catch potential of large pelagic fish in the Sulampua area. This study uses secondary data in the form of panel data obtained from the Central Statistics Agency. Data analysis of the influence of capture fisheries production on GRDP uses a multiple linear regression approach. Meanwhile, data analysis of the utilization level and sustainable catch potential of large pelagic fisheries uses the Gordon-Schaefer model. The results of the study indicate that the value of TCT capture fisheries production simultaneously influences the value of Sulampua's GRDP with the regression equation Y = 68280.60 - 0.317X1 + 7.513X2 + 15.142X3. Based on the analysis of sustainable catch calculations, tuna and skipjack tuna catches have not yet exceeded their sustainable limits, with values of 5,598,282 tons/year and 4,370,412 tons/year, respectively. Meanwhile, mackerel catches have exceeded their sustainable limits, with a value of 3,856,748 tons/year. The utilization and efforts to catch TCT in Sulampua waters are already at full capacity. Therefore, sustainable fisheries management efforts are needed. Keywords: CPUE; GRDP; Mackerel; Skipjack; Sulampua; Tuna